Do economic and financial integration stimulate economic growth? A critical survey - Ehigiamusoe Kizito Uyi; Lean Hooi Hooi (Economics: Journal Articles, 2019)
The recent vote by Britain to quit the European Union (EU) and the political pressures in some member countries to exit the EU necessitates a critical evaluation of the long-run economic benefits of economic integration or union to member countries. Consequently, this paper examines recent empirical studies on the nexus between economic integration and economic growth in developed and developing countries. It also investigates the literature concerning the impact of financial integration on economic growth. Evidence from the study shows that although other views exist, there is overwhelming support for the growthenhancing effects of economic integration, albeit common currency adoption has an insignificant effect on economic growth. The channels through which economic integration exerts its influence on economic growth include capital accumulation, productivity growth, trade, and financial integration. However, the study shows that the impact of financial integration on economic growth is inconclusive. Based on the findings, the study draws some implications and policy options.